Hedgehog signaling promotes basal progenitor expansion and the growth and folding of the neocortex - Wang, Lei (Nat Neurosci, 2016)
The unique mental abilities of humans are rooted in the immensely expanded and folded neocortex, which reflects the expansion of neural progenitors, especially basal progenitors including basal radial glia (bRGs, also called outer RGs) and intermediate progenitor cells (IPCs). Here, we show that constitutively active Shh signaling expanded bRGs and IPCs and induced folding in the otherwise smooth mouse neocortex, whereas the loss of Shh signaling decreased the number of bRGs and IPCs and the size of the neocortex. SHH signaling was strongly active in the human fetal neocortex but not in the mouse embryonic neocortex, and blocking SHH signaling in human cerebral organoids decreased the number of bRGs. Mechanistically, Shh signaling increased the initial generation and self-renewal of bRGs as well as increasing IPC proliferation. Thus, robust SHH signaling in the human fetal neocortex may contribute to bRG and IPC expansion and neocortical growth and folding.